2008
DOI: 10.1109/led.2008.923207
|View full text |Cite
|
Sign up to set email alerts
|

Low Turn-On Voltage and High-Current $\hbox{InP}/ \hbox{In}_{0.37}\hbox{Ga}_{0.63}\hbox{As}_{0.89}\hbox{Sb}_{0.11}/\hbox{In}_{0.53}\hbox{Ga}_{0.47}\hbox{As}$ Double Heterojunction Bipolar Transistors

Abstract: We report on the dc and microwave characteristics of an InP/In 0.37 Ga 0.63 As 0.89 Sb 0.11 /In 0.53 Ga 0.47 As double heterojunction bipolar transistor grown by solid-source molecular beam epitaxy. The pseudomorphic In 0.37 Ga 0.63 As 0.89 Sb 0.11 base reduces the conduction band offset ∆E C at the emitter/base junction and the base band gap, which leads to a very low V BE turn-on voltage of 0.35 V at 1 A/cm 2 . A current gain of 125 and a peak f T of 238 GHz have been obtained on the devices with an emitter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…For the past two decades, InP-based HBTs have attracted great interest for use in very high frequency applications such as 40 Gb s À1 optical communication systems. [18][19][20][21][22][23][24][25][26][27][28] The use of double heterostructures based on InP material systems has allowed larger breakdown voltages and bandwidths than was possible for SiGe bipolar transistors. Recently, aggressively scaled InP/InGaAs single heterojunction bipolar transistors (SHBTs) and InP double heterojunction bipolar transistors (DHBTs) have exhibited record current gain cutoff frequencies ( f T ) and power gain cutoff frequencies ( f MAX ) as high as 765 GHz and 1 THz, respectively.…”
Section: Sb-based Heterojunction Bipolar Transistors (A) Backgroundmentioning
confidence: 99%
“…For the past two decades, InP-based HBTs have attracted great interest for use in very high frequency applications such as 40 Gb s À1 optical communication systems. [18][19][20][21][22][23][24][25][26][27][28] The use of double heterostructures based on InP material systems has allowed larger breakdown voltages and bandwidths than was possible for SiGe bipolar transistors. Recently, aggressively scaled InP/InGaAs single heterojunction bipolar transistors (SHBTs) and InP double heterojunction bipolar transistors (DHBTs) have exhibited record current gain cutoff frequencies ( f T ) and power gain cutoff frequencies ( f MAX ) as high as 765 GHz and 1 THz, respectively.…”
Section: Sb-based Heterojunction Bipolar Transistors (A) Backgroundmentioning
confidence: 99%
“…Due to the difficulty in achieving higher base doping concentrations, the f MAX of these devices was lower than f T . Following this, many groups demonstrated GaInAsSb DHBTs with low turn-on and low offset voltages [57,58] which were realized due to a smaller bandgap (E g ) of the quaternary base and a reduced emitter-base (E/B) conduction band offset (∆E C ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, further reduction of the turn-on voltage is possible by employing a narrow-band-gap material such as InGaAsSb. 10,11) Chen et al 10) demonstrated InP/In 0:37 -Ga 0:63 As 0:89 Sb 0:11 HBTs that exhibit the turn-on baseemitter voltage (V BE ) as low as 0.35 V at collector current density (J C ) of 1 A/cm 2 . These HBTs were grown by molecular beam epitaxy (MBE) with Be as a p-type dopant.…”
Section: Introductionmentioning
confidence: 99%